BRICS immigration policies and visa regimes, strategic cooperation for a future BRICS African agenda - Arina Muresan (Journal of BRICS Studies)
Africa is a geostrategic point of interest for the BRICS. However, the BRICS have been severely criticised for how Africa is engaged; that the manner replicates the low levels of growth that other western partners had engaged in. It is up to the BRICS to act in accordance with the narrative that has been crafted in that it is a global partner for reform. This paper explores how the BRICS may make a meaningful contribution to its Africa outreach project and global economic reform through the analysis of BRICS’ immigration policies such as visa regimes to African countries in the context of a poly-pandemic world. The paper explores the international arena attempting to recover from the Covid-19 pandemic in the context of immigration policies and visa regimes as power levers, the BRICS’ position on migration and their strategic engagement with Africa.